THE NEGATIVE IMPACT OF THE NATURAL AND SOCIAL ENVIRONMENT ON CHILDREN'S BODIES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the impact of the environment on children's health and development. It analyzes the main environmental factors affecting children's physical, mental, and intellectual well-being. Particular attention is paid to air, water, and soil pollution, as well as the role of the social environment and the family in shaping children's health. The importance of a favorable ecological environment for the healthy development of the younger generation is emphasized. The article reviews modern environmental problems, their consequences for children, and ways to improve the ecological situation. It can be concluded that preserving children's health and ensuring environmental safety require the joint efforts of the state, society, and the family.
Keywords: Ecology, environment, children's health, air pollution, water pollution, environmental safety, physical development, mental health, social environment, healthy lifestyle, protection of children's health, sustainable development